Testicular histology of Anurans that deposit eggs out of the water - Pucci Alcaide, Ana (2020)
Anuran amphibians show the largest diversity of amphibian reproductive modes,many of which imply egg deposition out of the water. This kind of egg depositionrequires specialisations to avoid egg desiccation. Physiological, anatomical and ethological traits integrate to define these modes. In particular, morphological featuresof the urogenital system correlate with these reproductive modes and the environmental conditions where egg-laying occurs. In this study, we describe the testicularhistology and spermatogenesis of the nest-building frog Leptodactylus latinasus, andwe compare it with other species that breed out of water. We found variations in testis size, the thickness of interstitial tissue, tunica albuginea, and peritubular tunics,flagellum length, and in the shape and size of the spermatozoal nucleus. Certainspecifics? characters differed at the species level, but not between families. Suchvariation could be an indicator of spermatozoal performance and environmentalconstraints under which fertilisation takes place.